Monitoring student progress - Agency for Instructional Technology; Films for the Humanities (Firm) (Princeton, NJ : Films for the Humanities & Sciences, 2005)
Frequent and regular assessment of student progress is an effective method for driving schools towards equity and academic excellence. This program focuses on how student assessment data can be used to evaluate and improve instructional priorities and strategies, to communicate high expectations, and to involve parents and the community in a school's efforts
DVD Format
Keywords: Students -- Rating of -- United States; Students -- Rating of -- Canada; Educational tests and measurements -- United States; Educational tests and measurements -- Canada; Education -- Parent participation -- United States; Education -- Parent participation -- Canada; Parent-teacher relationships; School management and organization